2021
DOI: 10.3926/jiem.3334
|View full text |Cite
|
Sign up to set email alerts
|

Determinants factors of intention to adopt big data analytics in Malaysian public agencies

Abstract: Purpose: This research objective was to analyze factors affecting IT practitioners’ behavioral intentions in adopting (BDA) using a combination of Initial Trust Model (ITM), Unified Theory Of Acceptance And Use Of Technology (UTAUT) AND Task-Technology Fit (TTF) Model acceptance models.Design/methodology/approach: Using a cross sectional survey, empirical data were collected. A total of 200 questionnaires were obtained and screened. 14 insufficient answers were subsequently discarded leaving 186 valid structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…This significant relationship is consistent with previous research (Radovan & Kristl, 2017;Teo & Noyes, 2012), which concluded that performance expectancy is a key factor influencing teachers' intention to adopt new technologies. Other studies (Brünink, 2016;Sahid et al, 2021;Cabrera-Sanchez & Villarejo-Ramos, 2019) also found positive and significant effects of performance expectancy on the intention to use big data technology. This result implies that if educators believe that using big data technology will benefit their careers, they will be more likely to accept it.…”
Section: Discussion and Implications Determinants Of Acceptance Of Bi...mentioning
confidence: 81%
See 1 more Smart Citation
“…This significant relationship is consistent with previous research (Radovan & Kristl, 2017;Teo & Noyes, 2012), which concluded that performance expectancy is a key factor influencing teachers' intention to adopt new technologies. Other studies (Brünink, 2016;Sahid et al, 2021;Cabrera-Sanchez & Villarejo-Ramos, 2019) also found positive and significant effects of performance expectancy on the intention to use big data technology. This result implies that if educators believe that using big data technology will benefit their careers, they will be more likely to accept it.…”
Section: Discussion and Implications Determinants Of Acceptance Of Bi...mentioning
confidence: 81%
“…Furthermore, previous big data research has primarily focused on technical attributes (such as machine learning or technical algorithms) with little consideration given to the intention to use big data technologies in practice (Kwon et al, 2019). In addition, although a few studies have focused on the intentions of adopting big data techniques in organizations (Brünink, 2016;Demoulin & Coussement, 2020;Verma et al, 2018;Sahid et al, 2021;Queiroz & Pereira, 2019;Cabrera-Sanchez & Villarejo-Ramos, 2019), identifying the factors that influence educators' intentions to use big data technology in teaching needs more research.…”
Section: Introductionmentioning
confidence: 99%
“…Privacy or anonymity, from some standpoint, refers to the expectation of fairness and control over personal information and the expectation of confidentiality (Sahid et al, 2021). Privacy is also described as the ability of individuals to control the access others have to personal information about them.…”
Section: Privacymentioning
confidence: 99%
“…Earlier research has been undertaken to shed light on the value and framework concerning the adoption of BDA in diverse fields (Memon et al, 2017;Soon et al, 2016), public sector (Sahid et al, 2021;Weerakkody et al, 2017), and higher education (Brock & Khan, 2017). These studies highlighted the enablers that are important to be taken into consideration before establishing any BDA strategy.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in earlier studies, asserting attitudes toward innovation, particularly the study of users' perception of usefulness and ease of use, is a critical strategy (Sahid et al, 2021). Yet, if BDA cannot improve the user's performance on the job and is incompatible with the demands of their tasks, it may not be accepted.…”
Section: Introductionmentioning
confidence: 99%